The history of entrepreneurship in Mexico : contextualizing theory, theorizing context - Montiel Méndez, Oscar Javier (Emerald Publishing Limited, 2020)
Entrepreneurs develop based on their surroundings. It is easy to understand US entrepreneurs, with the wealth of information available about their development, but how does working in Mexico influence entrepreneurship, and emerging entrepreneurs? Exploring the history of Mexico's entrepreneurs, expert authors Araceli Almaraz Alvarado and Oscar Javier Montiel Méndez delve into the empirical and theoretical opportunities that emerge from this historical analysis. Current literature on Mexican entrepreneurship points out the importance of contextualising entrepreneurial lives, and asks us to look across agents, sectors and regions, to reach a better understanding of the trajectories of entrepreneurship in Mexico. Including chapters across different businesses in Mexico, the editors and contributors seek to expose the convergence between theory and practice. For students of business and international development, this is an unmissable text containing the most current research on Mexican entrepreneurship.